Asset management guidance for transportation agencies. - Markow, Michael J.; National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program (Washington, D.C. Transportation Research Board, National Research Council, 2002)
This digest announces interim results from NCHRP Project 20-24(11). The digest describes three agency reports prepared by Cambridge Systematics, Inc., assisted by Parsons Brinckerhoff Quade & Douglas, Inc.; Roy Jorgensen Associates, Inc; and Paul D. Thompson. The ... reports ... are available on the NCHRP website as Web Document 41. Michael J. Markow served as the Principal Investigator.
Caption title.
March 2002.
Keywords: Highway departments -- United States -- Management; Asset-liability management